Short-lived Technical Literatures: A Bibliometric Analysis - Worthen, D. B. (Methods of Information in Medicine, 1978)
Much work has been completed on the application of quantitative measures to literatures dealing with the subject area devoted to ideas or concepts. Little or no work has been reported on the use of these techniques in an applied situation, on a literature devoted to a scientific product. This study attempts to apply the quantitative measures to such a literature and examine some of the implications of the results in terms of professional action on the part of the librarian or information scientist. Bibliometric techniques developed on long-lived literatures are applicable to short-lived literatures devoted to a sample of two pharmaceutical products.
Keywords: Bibliometric Study; Drug Information; Information Betrieval